Penyediaan Denah Lokasi Dan Penguatan Pojok Literasi Masyarakat Berbasis Lingkungan - Sovia, Anggita; Salsabila, Rere; Wijaya, Riski Okta; Yerpi, Yerpi; Ningrum, Fadilla Dwi; Akbar, Abdussalam Al; Martiani, Martiani; Dahlia, Dahlia (LPPM Universitas Dehasen Bengkulu, 2026)
The problems faced by the community of RT 26 RW 07, Sawah Lebar Village, include limited information media on the layout of the area and low access to community literacy facilities. The absence of a map of the neighborhood makes it difficult for the community and newcomers to recognize the boundaries of the area and public facilities, while the lack of literacy facilities has an impact on low reading interest, especially among children and teenagers. This community service activity aims to improve the organization of regional information by providing location maps and to increase community interest in reading by providing literacy corners. The implementation method involves observation, regional data collection, information media design, and the provision and assistance of literacy corner utilization. The results of the activity show the availability of location maps at strategic points and the establishment of literacy corners that are utilized by the community. This program contributes to improving environmental order and community empowerment based on education.